Culture and “the heart of the inner life”, and psalms - Płuciennik, Jarosław (The Bible as a meeting place for Christian denominations, 2022)
In the article, the author gathers arguments for the central thesis: although the metaphor of the “heart of the inner life” has not appeared anywhere in its linguistic materiality, neither in Polish nor, for example, in the English, “the heart of the inner life”, this metaphor has many linguistic embodiments and linguistic and cultural in biblical and supra-denominational contexts. The phrase “culture and the heart of inner life” is thus a one-phrase formulation of this theoretical thesis: the heart in the psalmic Hebrew culture is not identical to the heart of modern times. It symbolizes the romantic-sentimental element of human anthropology. The heart in the psalms should be understood as synonymous with “life”, especially “inner life”, “mental life”, and its cultivation – meditation, thinking transformation. In this sense, the “religion of the heart” of the psalms is far from being sentimental and romanticizing emotions, elation and sublimity based solely on enthusiasm and ecstasy. Psalms are often mixed with modern poetry, in which the dominant function is the expression of emotions. The article may be of interest not only to scholars of psalms and the Bible in the contexts of national, Hebrew, Polish and English-speaking cultures but also to cultural philosophers and theorists of metaphors and rhetorical figures. The author bases his reflections on the main topic: “the culture and heart of the inner life” on a polyglot analysis of the verses of two psalms of the Polish ecumenical translation, Psalm 37 and 119. He confronts Polish and English translations of fragments of these psalms. The contextual work for interpretation of the thesis is “The Inner Land” by Eberhard Arnold. The polyglot analysis of several dozen examples confirms the central thesis of the existence of the metaphor “heart of inner life”.